Recent Advances in the Synthesis and Chemistry of Nitronates - Tabolin, Andrey A.; Sukhorukov, Alexey Yu.; Ioffe, Sema L.; Dilman, Alexander D. (Synthesis, 2017)
Due to their availability and versatile reactivity, nitronates have become important building blocks in the stereoselective synthesis of bioactive molecules. This short review provides a summary of recent developments on the synthesis, chemistry and applications of O-alkyl and O-silyl nitronates.1 Introduction2 Approaches to the Synthesis of Nitronates2.1 Synthesis of Six-Membered Cyclic Nitronates2.1.1 Formal [4+2] Approaches2.1.2 Formal [3+3] Approaches2.1.3 Other Approaches2.2 Synthesis of Five-Membered Cyclic Nitronates2.2.1 Formal [3+2] Approaches2.2.2 Formal [4+1] Approaches2.2.3 Oxidation Approaches3 Chemistry of Nitronates3.1 Nitronates as α-C-Nucleophiles3.2 Nitronates as α-C-Electrophiles3.3 Nitronates in [3+n]-Annulation Reactions3.4 Reactions Involving the β-Carbon Atom of Nitronates3.5 Miscellaneous Transformations4 Conclusion
Keywords: nitronates; nitroalkanes; cycloaddition; 1,3-dipoles; umpolung